Russian Warfare Strategies: An In-Depth Analysis - Serafim Pavel (GoAcademica Research & Publishing, 2023)
Russia's role in global geopolitics has been a subject of perennial interest and concern. A vast expanse of land spanning two continents, a rich history of military prowess, and a complex relationship with the Western world make Russia a formidable and enigmatic player in the international arena. The Russian Federation, as the successor state of the Soviet Union, continues to wield significant influence through a combination of conventional and unconventional warfare strategies. This scientific journal article aims to provide an in-depth exploration of the multifaceted strategies employed by Russia in the realm of warfare. From historical perspectives to contemporary tactics, this paper endeavors to unravel the intricacies of Russia's approach to conflict.